2016
DOI: 10.1007/s12035-016-9944-9
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Mitochondrial Biogenesis and Fission/Fusion Mediated by PGC-1α Regulates Rotenone-Induced Dopaminergic Neurotoxicity

Abstract: Parkinson's disease is a common neurodegenerative disease in the elderly, and mitochondrial defects underlie the pathogenesis of PD. Impairment of mitochondrial homeostasis results in reactive oxygen species formation, which in turn can potentiate the accumulation of dysfunctional mitochondria, forming a vicious cycle in the neuron. Mitochondrial fission/fusion and biogenesis play important roles in maintaining mitochondrial homeostasis. It has been reported that PGC-1α is a powerful transcription factor that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(77 citation statements)
references
References 43 publications
3
73
1
Order By: Relevance
“…We have previously reported acute loss of mitochondrial membrane potential (quantified using MitoTracker ® ; Smirnova et al 2016) which could lead to fission defects. Studies have shown that inhibition of mitochondrial fission or promotion of mitochondrial fusion has protective effects in rotenone-induced neurotoxicity (Peng et al 2017), and studies have documented rotenone-induced effects on mitochondrial trafficking and movement (Fang et al 2016; Haddad and Nakamura 2015; Borland et al 2008). Mitochondria undergo dynamic changes using fusion and fission to maintain function and morphology during stress (Knott et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported acute loss of mitochondrial membrane potential (quantified using MitoTracker ® ; Smirnova et al 2016) which could lead to fission defects. Studies have shown that inhibition of mitochondrial fission or promotion of mitochondrial fusion has protective effects in rotenone-induced neurotoxicity (Peng et al 2017), and studies have documented rotenone-induced effects on mitochondrial trafficking and movement (Fang et al 2016; Haddad and Nakamura 2015; Borland et al 2008). Mitochondria undergo dynamic changes using fusion and fission to maintain function and morphology during stress (Knott et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria undergo dynamic changes using fusion and fission to maintain function and morphology during stress (Knott et al 2008). Imbalances in these mechanisms and fragmented mitochondria have been found in PD patients and only recently in vitro (Reddy 2008; Peng et al 2017). The analysis of mitochondria number also allowed us to confirm that the differences observed in complex I activity and ATP were not due to changes in the number of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, mitochondrial fission leads to the production of small mitochondrial fragments, resulting in lower MMP. In several disease models, such as Parkinson’s or Huntington’s diseases, relatively more mitochondrial fissions are observed in diseased neuronal cells (Manczak and Reddy, 2015; Peng et al, 2016). Furthermore, our truncated ATXN3 model also revealed more mitochondrial fissions ( Figure 3 ), suggesting that mitochondrial fission is a common characteristic of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The outer mitochondrial membrane family of fusion and fission proteins has recently garnered significant interest in multiple aspects of mitochondrial function (Chen et al, 2010; Cho et al, 2010; Elgass et al, 2013; Huang et al, 2007; Peng et al, 2017; Poole et al, 2008; Youle and van der Bliek, 2012; Yue et al, 2014). There has been a much greater focus on fission proteins and their role in disease than on fusion proteins (Corazao-Rozas et al, 2016; Elgass et al, 2013; Youle and van der Bliek, 2012).…”
Section: Discussionmentioning
confidence: 99%